A computational analysis on convective heat transfer for impinging slot nanojets onto a moving hot body - Cosanay, Hakan; F. Öztop, Hakan Fehmi; Selimefendigil, Fatih (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this study is to perform computational analysis on the steady flow and heat transfer due to a slot nanojet impingement onto a heated moving body. The object is moving at constant speed and nanoparticle is included in the heat transfer fluid. The unsteady flow effects and interactions of multiple impinging jets are also considered. Design/methodology/approach The finite volume method was used as the solver in the numerical simulation. The movement of the hot body in the channel is also considered. Influence of various pertinent parameters such as Reynolds number, jet to target surface spacing and solid nanoparticle volume fraction on the convective heat transfer characteristics are numerically studied in the transient regime. Findings It is found that the flow field and heat transfer becomes very complicated due to the interaction of multiple impinging jets with the movement of the hot body in the channel. Higher heat transfer rates are achieved with higher values of Reynolds number while the inclusion of nanoparticles resulted in a small impact on flow friction. The middle jet was found to play an important role in the heat transfer behavior while jet and moving body temperatures become equal after t = 80. Originality/value Even though some studies exist for the application of jet impingement heat transfer for a moving plate, the configuration with a solid moving hot body on a moving belt under the impacts of unsteady flow effects and interactions of multiple impinging jets have never been considered. The results of the present study will be helpful in the design and optimization of various systems related to convective drying of products, metal processing industry, thermal management in electronic cooling and many other systems.
Keywords: Heat transfer; Moving plate; Moving body; Impinging jet; Nanojet